Innovative technologies for identifying oral potentially malignant disorders: a systematic review - Supraja Salwaji; Mohan Kumar Pasupuleti; Ravikanth Manyam; Swetha Pasupuleti; Hande Uzunçıbuk; Diana Russo; Gabriele Cervino; Maria Maddalena Marrapodi; Giuseppe Minervini (Exploration of Medicine)
Background: Early detection of precancerous oral lesions is crucial for preventing oral cancer. Traditional visual inspections have limitations, prompting the development of advanced technologies to improve detection accuracy. The study focused on evaluating and summarizing recent advancements in optical, molecular, and digital technologies used for the identification of oral potentially malignant disorders (OPMDs). Methods: A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science, focusing on studies published in English between 2014 and 2024. The search targeted pioneering research addressing key challenges in OPMD detection. Selection criteria prioritized innovative approaches for identifying potentially malignant oral lesions. Results: The initial search yielded 359 studies, with 10 meeting the inclusion criteria for in-depth analysis. These studies highlight emerging technologies that enhance early detection, including molecular biomarkers for analyzing genetic and protein alterations, liquid biopsy for detecting circulating tumor DNA (ctDNA), and AI-assisted diagnostics. Additionally, fluorescence spectroscopy and optical coherence tomography (OCT) improve detection accuracy, enabling early interventions and better patient outcomes. Conclusions: The systematic review underscores the growing significance of innovative technologies in the early identification of OPMDs. Advances in optical methods such as fluorescence spectroscopy and OCT, molecular techniques including biomarker analysis and liquid biopsy, and digital innovations like AI-driven diagnostics offer substantial improvements over conventional visual inspection. These technologies not only enhance detection accuracy but also hold promise for earlier diagnosis and improved clinical outcomes. Continued research and validation are essential to translate these emerging tools into routine clinical practice, ensuring timely intervention and effective prevention of oral cancer.